Congenital anterior urethral diverticulum in children: case series and review of the literature - Rajat Piplani; Samir K. Acharya; Deepak Bagga (SpringerOpen, 2023)
Abstract Background Congenital anterior urethral diverticulum (CAUD) is a rare condition in children. This condition can present at any age; however, it is more commonly identified in infants and older children. The patient may present with difficulty in micturition, dribbling of urine, poor urinary stream, or urinary tract infection. Children with large anterior urethral diverticulum with poor spongiosal support may also complain of cystic ventral penile swelling during micturition. Methods In this series, we report seven such cases of congenital anterior urethral diverticulum treated over a period of 12 years (2008-2020). All cases presented to the Pediatric Surgery Department with dysuria, dribbling of urine, recurrent urinary tract infection, and/or fluctuant ventral penile swelling. They were further evaluated with retrograde urethrography with micturating cysto-urethrogram and cysto-urethroscopy. Results Three cases had anterior urethral valves that were managed by cystoscopic fulguration of valves. Surprisingly, all these three cases had concomitant posterior urethral valves, while the other four cases presented with relatively larger and saccular anterior urethral diverticulum required excision of the diverticulum and primary urethral reconstruction. Conclusions The cases with congenital anterior urethral diverticulum secondary to anterior urethral valves may also be associated with posterior urethral valves as seen in our case series. Surgeons should be aware of this association, and both valves should be fulgurated in the same sitting. A larger and saccular anterior urethral diverticulum requires excision and urethroplasty as a definitive procedure.